Time-course of time-motion, physiological, perceived exertion and neuromuscular responses during simulated judo matches - Ferreira Julio, U.; Panissa, V.; Agostinho, M. F.; Cury, R.; Del Conti Esteves, J. V.; Franchini, E. (International Journal of Performance Analysis in Sport, 2018)
The objective of the present study was to describe the physiological, perceived exertion, time-motion and neuromuscular responses in judo matches with different durations. Twelve male brown and black belt judo athletes (74.3 ± 10.5 kg, 175.1 ± 5.3 cm) performed five matches with different durations (1, 2, 3, 4 and 5 min) randomly determined, against the same opponent, in different days and blinded to the time duration. Data from matches were analyzed concerning: rating of perceived recovery, rating of perceived exertion (RPE), heart rate, delta of blood lactate concentrations [La] (the highest minus the rest values), rate of the increment in RPE and [La] per minute of match, maximal isometric strength in dominant and non-dominant hands, leg power and dynamic strength-endurance. After the match, decreases in dynamic strength-endurance and non-dominant isometric strength were observed, dominant hand isometric strength was maintained, while leg power increased. The rate of the physiological and perceptual responses per minute of match changes decreased throughout the course of the match, with the highest changes occurring at the beginning of match and none time-motion variable has been modified throughout the course of the match.